The chambered tombs of the Isle of Man : a study by Audrey Henshall 1969-1978 - Henshall, A. S. (Archaeopress Publishing Ltd, 2017)
This title is devoted to the chambered tombs of the Isle of Man and, though there are no more than nine surviving monuments, they are of considerable interest and importance because of the central location of the island in the north Irish Sea where cultural influences and traditions of tomb building are mixed.